Day 1 Mon, May 01, 2017 2017
DOI: 10.4043/27541-ms
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Site Response Analyses of Bay of Campeche Clay Using Predicted Dynamics Soil Properties

Abstract: Seismic site response analyses are an important first step in the seismic evaluation of fixed offshore platforms in the Bay of Campeche. This analysis is used to estimate ground motions for the development of design response spectra, dynamic stresses, strains, and displacements within the soil profile and liquefaction hazard analyses. Seismic site response analyses of a clayey deposit located in the Bay of Campeche is performed using predicted dynamic soil properties, including the in-situ shear wave velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The discrepancies in damping ratio between the damping ratio curve developed in the present study for the Bay of Campeche clay and Darendeli (2001) curve can produce large differences when they are used to perform earthquake response analyses, as observed by Taboada, et al, (2017b) giving lower amplification of accelerations that are unconservative for the case when the Darendeli (2011) damping curve is utilized.…”
Section: Comparison With Previously Published Models For Claysmentioning
confidence: 82%
See 1 more Smart Citation
“…The discrepancies in damping ratio between the damping ratio curve developed in the present study for the Bay of Campeche clay and Darendeli (2001) curve can produce large differences when they are used to perform earthquake response analyses, as observed by Taboada, et al, (2017b) giving lower amplification of accelerations that are unconservative for the case when the Darendeli (2011) damping curve is utilized.…”
Section: Comparison With Previously Published Models For Claysmentioning
confidence: 82%
“…The equations developed to calculate VS, and the curves of G/Gmax- and D- of Bay of Campeche clays are recommended for preliminary or perhaps even final seismic site response evaluations. It has been shown that they can be used in practice to perform earthquake response analysis in the Bay of Campeche and determine the design acceleration spectrum at the depth of maximum soil-pile interaction (Taboada, et al, 2017b;Taboada, et al, 2022).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%